Evolution of the galaxy correlation function at redshifts 0.2 < z < 3. Issue Volume 11:Issue S308(2015) (12th October 2016) - Sołtan, Andrzej M.
Abstract: We determine the auto-correlation function (ACF) of galaxies using massive deep galaxy surveys for which distances to individual objects are assessed using photometric redshifts. The method is applied to the 2deg COSMOS survey of ~ 300000 galaxies with i + < 25 and z ph ≲ 3. The distance estimates based on photometric redshifts are not sufficiently accurate to be directly used to determine the ACF. Nevertheless, the photometric redshifts carry statistical information on the data distribution on (very) large scales. The investigation of the surface distribution of galaxies in several redshift (=distance) bins allows us to determine the spatial (3D) ACF over the redshift range of 0.2 - 3.2 or look back time of 2.4 - 11.5 Gy.